A successful model of road traffic injury surveillance in a developing country: process and lessons learnt - Razzak Junaid; Shamim Muhammad; Mehmood Amber; Hussain Syed; Ali Mir; Jooma Rashid (BMC, 2012)
Abstract Background Road Traffic Injuries (RTIs) are one of the leading causes of death and disability worldwide with 90% of global mortality concentrated in the low and middle income countries. RTI surveillance is recommended to define the burden, identify high risk groups, plan intervention and monitor their impact. Despite its stated importance in the literature, very few examples of sustained surveillance systems are reported from low income countries. This paper shares the experience of setting up an urban RTI surveillance program in the emergency departments of five major hospitals in Karachi, Pakistan. Method We describe the process of establishing a surveillance system including assembling a multi-institution research group, developing a data collection methodology, carrying out data collection and analysis and dissemination of information to the relevant stakeholders. In the absence of a road safety agency, the surveillance system required developing individual partnerships with industry, police, city government, media and many other stakeholders. Impact of the surveillance is demonstrated by some initiatives in the local trauma system and improvements in road design to effect hazard reduction. Conclusion We demonstrated that a functional RTI surveillance program can be established, and effectively managed in a developing country, despite lack of infrastructure and limitation of resources. Data utilization in the absence of well defined road safety infrastructure within the government is a challenge. More effective actions are hampered by the limited capacity in the transport and health sectors to do in-depth analysis through road safety audits and trauma registries.